Hubungan Tingkat Pengetahuan Keluarga Tentang Diit Hipertensi dan Tingkat Stres Dengan Frekuensi Kekambuhan Hipertensi Pada Lansia - Senoaji, Ahmad Umar, H. M. Abi Muhlisin, S.K.M., M.Kep (2017)
Elderly with hypertension is The Group has a Risk to a good quality of life. One of it caused by the recurrence of hypertension. Regression of elderly's ability in cognitive and psychomotor causing they need the help of others in maintaining the quality of life. Family is one of them. The ability of families in caring for the elderly determined by the family knowledge about diet of hypertension. Internally recurrence of hypertension in the elderly is also caused by distress that make sleep patterns of elderly disturbed and increase the blood pressure that causing the recurrence of hypertension. The purpose of this study is to knowing the corellation of family knowledge about hypertension diet and stress with incidence of hypertension recurrence in elderly at Pabelan village Puskesmas Kartasura Sukoharjo. This research is a correlative descriptive with cross sectional approach. The population of this research are 74 elderly with hypertension and experiencing recurrent of hypertension and also active participating in Posyandu activities in pabelan village. all the population are sampled with total sampling. Collecting data using questionnaires and the data was analysis using correlation and multiple linear regression. The Conclusion of the study are the level of family knowledge about hypertension diet is mostly lacking (50%), the stress level of hypertension patients are mostly heavy (51%), the frequency of recurrence of hypertension in patients with hypertension are mostly frequent (61%), There is a significant correlation of the level of family knowledge about hypertension diet with the frequency of recurrence of hypertension (p-value 0.001), there is a significant correlation beetwen stress level and the frequency of recurrence of hypertension (p-value 0.002), and the level of family knowledge about diet of hypertension is more dominant factor than stress level with frequency recurrence of hypertension in elderly at pabelan village Puskesmas Kartasura Sukoharjo.